2010
DOI: 10.1182/asheducation-2010.1.295
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Gammopathy of Undetermined Significance and Smoldering Myeloma: New Insights into Pathophysiology and Epidemiology

Abstract: Routine screening for monoclonal gammopathy of undetermined significance (MGUS) is not indicated. Despite this fact, MGUS is a common finding in medical practice. Almost all individuals diagnosed with MGUS represent incidental cases diagnosed when physicians order serum protein electrophoresis, immunofixation, or both, as part of the work-up of a number of common symptoms and laboratory abnormalities. In the absence of reliable molecular predictors of outcome, the detection of an early precursor state typicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 67 publications
2
20
0
3
Order By: Relevance
“…Previous studies have estimated that as many as 10% of patients with SS and monoclonal gammopathy develop hematological neoplasia [20]. This association depends on the mIg isotype, with IgM being the most common class associated with B-cell lymphoma and IgG with MM (in other series) [38], as reported in patients with MGUS [13]. However, strikingly, no patient developed MM in our series.…”
Section: Discussionsupporting
confidence: 40%
See 2 more Smart Citations
“…Previous studies have estimated that as many as 10% of patients with SS and monoclonal gammopathy develop hematological neoplasia [20]. This association depends on the mIg isotype, with IgM being the most common class associated with B-cell lymphoma and IgG with MM (in other series) [38], as reported in patients with MGUS [13]. However, strikingly, no patient developed MM in our series.…”
Section: Discussionsupporting
confidence: 40%
“…Therefore, monoclonal gammopathy should be considered as a frequent immunological marker of primary SS. Recent studies of patients with MGUS have suggested a prognostic role for the isotype of the monoclonal band, and the Mayo Clinic prognostic model has included a non-IgG isotype as a risk factor for multiple myeloma [13]. The predominant isotype in our primary SS patients was IgGk, as was also found in the abovementioned meta-analysis [20] and in large series of patients with MGUS [35].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…10 Approximately 1% of patients with MGUS transform into symptomatic plasma cell disorders annually. 11 An initial paraprotein or M-protein concentration of >15 g/L, the detection of an IgM or IgA paraprotein, and an abnormal free-lightchain ratio (free kappa/lambda ratio; normal range = 0.26-1.65) are related to an increased risk of a malignant evolution. 8,12 In patients with MGUS presenting with peripheral neuropathy, progressive weight loss, progression of the neuropathy, and an M-protein level of >1 g/L also have been identified as independent predictors for a malignant transformation.…”
Section: Neuropathy Associated With Mgusmentioning
confidence: 99%
“…51 The diagnosis of MM is usually based on the following clinical findings: (1) serum M-protein, (2) BenceJones proteinuria, (3) increased bone-marrow plasma cells (≥10%), and (4) evidence of end-organ damage, such as hypercalcemia (serum calcium ≥ 11.5 mg/dL), renal insufficiency (serum creatine >1.73 mmol/L), anemia (normochromic, normocytic with a hemoglobin level of >2 g/dL below the lower limit of normal, or a hemoglobin level of <10 g/dL), or osteolytic bone lesions. 8,11 About 50% of patients have an…”
Section: -44mentioning
confidence: 99%